Multiplicity dependence of charged-particle intra-jet properties in pp collisions at √s=13 TeV - Acharya, S.; Adamova, D.; Rinella, G. Aglieri; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S. U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (SPRINGER, 2024)
The first measurement of the multiplicity dependence of intra-jet properties of leading charged-particle jets in proton-proton (pp) collisions is reported. The mean charged-particle multiplicity and jet fragmentation distributions are measured in minimum-bias and high-multiplicity pp collisions at center-of-mass energy root s = 13 TeV using the ALICE detector. Jets are reconstructed from charged particles produced in the midrapidity region (|eta| < 0.9) using the sequential recombination anti-kT algorithm with jet resolution parameters R = 0.2, 0.3, and 0.4 for the transverse momentum ( p(T)) interval 5-110 GeV/c. The high-multiplicity events are selected by the forward V0 scintillator detectors. The mean charged-particle multiplicity inside the leading jet cone rises monotonically with increasing jet pT in qualitative agreement with previous measurements at lower energies. The distributions of jet fragmentation function variables z(ch) and xi(ch) are measured for different jet- pT intervals. Jet- pT independent fragmentation of leading jets is observed for wider jets except at high- and low-z(ch) values. The observed hump-backed plateau structure in the. ch distribution indicates suppression of low- p(T) particles. In high-multiplicity events, an enhancement of the fragmentation probability of low-zch particles accompanied by a suppression of high-z(ch) particles is observed compared to minimum-bias events. This behavior becomes more prominent for low- p(T) jets with larger jet radius. The results are compared with predictions of QCD-inspired event generators, PYTHIA8 with Monash 2013 tune and EPOS LHC. It is found that PYTHIA8 qualitatively reproduces the jet modification in high-multiplicity events except at high jet p(T). These measurements provide important constraints to models of jet fragmentation.
Keywords: PROTON-PROTON COLLISIONS; PB COLLISIONS; PERTURBATIVE QCD; CROSS-SECTIONS; PARTON; DISTRIBUTIONS; CENTRALITY; SHAPES; ENERGY; Physics